The role of "mixed" orexigenic and anorexigenic signals and autoantibodies reacting with appetite-regulating neuropeptides and peptides of the adipose tissue-gut-brain axis: relevance to food intake and nutritional status in patients with anorexia nervosa and bulimia nervosa - Smitka, Kvido; Papezova, Hana; Vondra, Karel; Hill, Martin; Hainer, Vojtech; Nedvidkova, Jara (International journal of endocrinology, 2013)
Eating disorders such as anorexia (AN) and bulimia nervosa (BN) are characterized by abnormal eating behavior. The essential aspect of AN is that the individual refuses to maintain a minimal normal body weight. The main features of BN are binge eating and inappropriate compensatory methods to prevent weight gain. The gut-brain-adipose tissue (AT) peptides and neutralizing autoantibodies play an important role in the regulation of eating behavior and growth hormone release. The mechanisms for controlling food intake involve an interplay between gut, brain, and AT. Parasympathetic, sympathetic, and serotoninergic systems are required for communication between brain satiety centre, gut, and AT. These neuronal circuits include neuropeptides ghrelin, neuropeptide Y (NPY), peptide YY (PYY), cholecystokinin (CCK), leptin, putative anorexigen obestatin, monoamines dopamine, norepinephrine (NE), serotonin, and neutralizing autoantibodies. This extensive and detailed report reviews data that demonstrate that hunger-satiety signals play an important role in the pathogenesis of eating disorders. Neuroendocrine dysregulations of the AT-gut-brain axis peptides and neutralizing autoantibodies may result in AN and BN. The circulating autoantibodies can be purified and used as pharmacological tools in AN and BN. Further research is required to investigate the orexigenic/anorexigenic synthetic analogs and monoclonal antibodies for potential treatment of eating disorders in clinical practice.